Conserved size and periodicity of pyramidal patches in layer 2 of medial/caudal entorhinal cortex. Issue 4 (9th September 2015) - Naumann, Robert K.; Ray, Saikat; Prokop, Stefan; Las, Liora; Heppner, Frank L.; Brecht, Michael
ABSTRACT: To understand the structural basis of grid cell activity, we compare medial entorhinal cortex architecture in layer 2 across five mammalian species (Etruscan shrews, mice, rats, Egyptian fruit bats, and humans), bridging ∼100 million years of evolutionary diversity. Principal neurons in layer 2 are divided into two distinct cell types, pyramidal and stellate, based on morphology, immunoreactivity, and functional properties. We confirm the existence of patches of calbindin‐positive pyramidal cells across these species, arranged periodically according to analyses techniques like spatial autocorrelation, grid scores, and modifiable areal unit analysis. In rodents, which show sustained theta oscillations in entorhinal cortex, cholinergic innervation targeted calbindin patches. In bats and humans, which only show intermittent entorhinal theta activity, cholinergic innervation avoided calbindin patches. The organization of calbindin‐negative and calbindin‐positive cells showed marked differences in entorhinal subregions of the human brain. Layer 2 of the rodent medial and the human caudal entorhinal cortex were structurally similar in that in both species patches of calbindin‐positive pyramidal cells were superimposed on scattered stellate cells. The number of calbindin‐positive neurons in a patch increased from ∼80 in Etruscan shrews to ∼800 in humans, only an ∼10‐fold over a 20, 000‐fold difference in brain size. The relatively constant size of calbindin patches differs from cortical modules such as barrels, which scale with brain size. Thus, selective pressure appears to conserve the distribution of stellate and pyramidal cells, periodic arrangement of calbindin patches, and relatively constant neuron number in calbindin patches in medial/caudal entorhinal cortex. J. Comp. Neurol. 524:783–806, 2016. © 2015 The Authors. The Journal of Comparative Neurology Published by Wiley Periodicals, Inc. Abstract : We studied patches of calbindin‐positive pyramidal cells in the medial entorhinal cortex using quantitative anatomy in five mammalian species. From the smallest mammals to humans, we found a similar periodic arrangement of calbindin patches, conserved patch size, and cell number per patch, whereas patch number and cholinergic innervation pattern varied across species.